Pengaruh Karakteristik Perusahaan Terhadap Corporate Social Responsibility Dengan Growth Sebagai Variabel Moderasi - Yura Karlinda Wiasa Putri; I Made Endra Lesmana Putra (Jurnal Widya Akuntansi dan Keuangan, 2024)
Corporate Social Responsibility (CSR) is a concept where companies take responsibility for the social, environmental and economic impacts of their business operations. This research aims to determine and obtain empirical evidence of the influence of company size, company age, leverage and company growth on the corporate social responsibility of manufacturing companies listed on the BEI in 2019-2021. The sample in this research was 30 MANUFACTURING companies listed on the Indonesia Stock Exchange in 2019-2021. Determination of the sample using the purposive sampling method. The analysis technique used is MRA. The research results show that growth is only able to moderate the relationship between company age and CSR, and is not able to moderate the direct relationship between size and leverage.